A STUDY ON INDONESIAN K-POPERS’ LITERACY ACTIVITIES IN ONLINE ENGLISH FANFICTION COMMUNITY - Rosalina; Suhatmady, Bibit; Surya, Satywati (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
The purposes of this study are (1) to know the motivation of Indonesian K-Poper to involve in online English fanfiction community, (2) to know what literacy activities that Indonesian K-Poper was engaged with in online English fanfiction community which focuses on the writing strategies uses by a fanfiction writer and what interaction that most frequently happens between the fanfiction writer and readers.The research applies a descriptive study with qualitative approach using New Literacy Study or NLS theory (Lankshear&Knobel, 2006; Black, 2006; Thomas; 2006) as its core. The data is taken from questionnaire, interview, and documentation of three fanfiction writers from asianfanfics.com. The result reveals four major findings. First, the subjects’ motivations in writing English fanfiction are divided into three different categories, such as; self-enrichment, to stay a little longer, and celebration of media content. Second, the literacy activities that the fanfiction writers in asianfanfics.com were engaged with majorly are reading each other’s fanfictionand posting or writing fanfiction. Furthermore, based on the analysis using Woodrow’s theory of writing strategy, they use Cognitive, Meta-cognitive, and Social category. Moreover, according to the result, the interaction that is mostly happened between the subject and their readers is social interaction which fell under two different indicators; compliment and appreciation.